Discourses of teacher autonomy and the role of teachers in Estonian, Finnish and Bavarian teachers' newspapers in 1991–2010. (November 2018) - Erss, Maria; Kalmus, Veronika
Abstract: This paper examines the construction of the professional role of teachers as reflected in the teacher autonomy and control discourses in teachers' newspapers during 1991–2010 in three national contexts: Estonia, Finland and Bavaria (Germany). Despite similar global pressures to increase the efficiency of education through output standardization and marketization, the local teaching traditions and policies have shaped different cultures of teacher professionalism. Throughout the national experiments with decentralization and recentralization of education, Estonian and Bavarian teachers have maintained restricted professionalism while Finnish teachers achieved extended professionalism in terms of the desired amount of teacher autonomy. Highlights: Events in the social and political environment influence the autonomy discourse. The political response to PISA has been a stronger evaluation and control discourse. The Finnish newspaper advocates an extended concept of teacher professionalism. Restricted professionalism can be preferable if sufficient resources are provided.